ARABIC: THE LANGUAGE OF RELIGION AND TECHNOLOGICAL PROGRESS - M. Dzaki Sholihin; Marhama Salwa; Lolita Sari Siregar; Sahkholid Nasution (Jurnal Recoms, 2025)
This study aims to identify and explain the origins and evolution of the Arabic language from a historical and academic perspective, as well as to analyze its contribution in Indonesia from the time Islam entered the country until the digital age. In addition, this study seeks to evaluate the challenges and opportunities in learning Arabic today, as well as to describe its contribution in the fields of education and knowledge. Through this study, it is hoped that the importance of the Arabic language will be evident, not only in a religious context but also in academic aspects and on the global stage. This research uses a qualitative method, a structured and systematic research method that aims to investigate, select, evaluate, and integrate relevant literature from various sources. This research also uses a library research approach that focuses on collecting and analyzing data from various literature sources, such as books, scientific journals, articles, official documents, and other relevant written sources. The analysis results show the history and development of the Arabic language and its influence on education, science, and the digital age. Historically, there are two views on the origin of the Arabic language: as the language used by Prophet Adam and as part of the Semitic language family. In Indonesia, the presence of the Arabic language began to increase with the arrival of Islam, then declined during the colonial period, and revived after Indonesia gained independence. In the digital age, Arabic faces various challenges and new opportunities through the use of technology for learning. In addition to its role as a religious language, Arabic also plays an important role in academia and scientific development, and contributes to the formation of a generation capable of competing globally.